Estimativa de um índice de estresse hídrico para a cultura da cana-de-açúcar com base na temperatura foliar - Trentin, Roberto (2010)
The objective of this work was to evaluate the behavior of leaf temperature and transpiration of sugarcane under different matric and meteorological conditions to estimate a crop water stress index (IEHC), which can be applied in irrigation management and estimates of productivity. Because of the need to apply water stress to plants, the experiment was conducted in a greenhouse, belonging to the Agricultural Engineering Department at the Federal University of Viçosa, Viçosa, MG, Brazil. Bud chips of sugarcane (cv. RB867515) were planted on May 6, 2009, in plastic pots with a capacity of 10 liters, which were filled with a commercial substrate. In total, 192 plants were grown for 6 months within the greenhouse, but only a portion was used in measurements. To evaluate the effect of water availability on leaf temperature and transpiration, under different meteorological conditions, three classes of water tension (Ψ) were maintained in the substrate: no water stress (Ψ < 0,5 bar), moderate (4,0 < Ψ < 6,0) and severe (Ψ > 11,0 bars) water stress. A meteorological data acquisition system was implemented for measuring global solar radiation (Rg), air velocity (U), air relative humidity (UR), air temperature (tar) and transpiration of three individual plants randomly chosen. In addition, leaf temperature (tc) was obtained by positioning an infrared thermometer at three different points of each plant used in the transpiration measurements. Based on the measurements obtained without water stress, it was found that the leaf temperature followed fluctuations of solar radiation caused by conditions of partly cloudy sky. In general, tc was lower than tar under no water stress conditions, with maximum difference of 6ºC. The effect of water stress on leaf temperature and transpiration was determined from the suspension of irrigation, by performing three measurement campaigns, initiated at 122, 150 and 181 days after planting, with two days intervals, until the water tension in the substrate reached 15 bars. Under severe water stress conditions, tc became 6.8°C higher than t ar. By using regression analysis, relations were established between the differential tc-tar and the variables global solar radiation (Rg) and air water vapor pressure deficit (DPVar), in order to determine the parameters necessary for obtaining the IEHC